(untitled) (Bangladesh Pharmaceutical Journal, 2019)
The aim of this research was to find out the phytochemical constituents and to evaluate the antibacterial, antioxidant, antidiarrheal and antipyretic activities of different extracts of Duabanga grandiflora. Antibacterial study was carried out by the disk diffusion method where the n-hexane extract showed the inhibitory activity against Staphylococcus aureus (12.3 mm) and Bacillus cereus (11.3 mm) as compared to standard drug ciprofloxacin. A quantitative antioxidant assay was done by DPPH free radical scavenging activity, where at the dose of 100 μg/ml the different extracts of D. grandiflora leaves revealed the highest inhibition of 81.07, 82.48, and 80.33%, respectively in comparison to standard ascorbic acid (86.9%). The ethanol extract showed IC50 value 1.91 μg/ml, which was found to be as potent as standard ascorbic acid (1.90 μg/ml). In antidiarrheal activity test by using castor oil induced diarrheal mice, the result showed different extracts (500 μg/ml) of plant possessed moderate antidiarrheal activity. It significantly increased the latency period and reduced the number fecal count in comparison to standard drug loperamide 3mg/kg body weight. In antipyretic activity test by using Brewer’s yeast induced pyrexia in Swiss albino mice the different extracts of D. grandiflora demonstrated mild to moderate antipyretic activity as compared to standard paracetamol Bangladesh Pharmaceutical Journal 22(1): 68-72, 2019